Sleep and Autonomic Manifestations in Parkinson’s Disease Complicated With Probable Rapid Eye Movement Sleep Behavior Disorder - Fujita, Hiroaki; Shiina, Tomohiko; Sakuramoto, Hirotaka; Nozawa, Narihiro; Ogaki, Keitaro; Suzuki, Keisuke (Frontiers in Neuroscience, 2022)
Patients with Parkinson’s disease (PD) complicated with rapid eye movement sleep behavior disorder (RBD) present with distinct clinical features. The purpose of this study was to determine the clinical features of sleep and autonomic symptoms in PD patients with probable RBD (pRBD). The study included 126 patients with PD. pRBD was defined as having a history of dream-enacting behavior with a total score of 5 or greater on the Japanese version of the RBD Screening Questionnaire (RBDSQ-J). The PD Sleep Scale-2 (PDSS-2) was used to evaluate sleep disturbances. Scales for Outcomes in PD-Autonomic dysfunction (SCOPA-AUT) were used to evaluate autonomic symptoms. Clinical assessments included disease severity, motor symptoms, olfaction, depression, cognitive function, levodopa equivalent dose (LED), and cardiac metaiodobenzylguanidine (MIBG) scintigraphy. Correlations between RBDSQ-J total scores and clinical variables were analyzed. Compared to PD patients without pRBD, PD patients with pRBD showed severe hyposmia, severe sleep-related symptoms, severe dysautonomia, and more reduced cardiac MIBG scintigraphy. Within the PDSS-2, the “PD symptoms at night” domain was significantly more severe in PD patients with pRBD. Within the SCOPA-AUT, the “urinary” and “cardiovascular” domains were significantly higher in PD patients with pRBD. In correlation analyses, RBDSQ-J total scores were positively correlated with PDSS-2 total scores, “PD symptoms at night” and “disturbed sleep” domains, Epworth Sleepiness Scale scores, SCOPA-AUT total scores, “urinary”, “cardiovascular” and “thermo” domain scores, and LED. RBDSQ-J total scores were negatively correlated with cardiac MIBG scintigraphy uptake. Binary logistic regression analysis showed that PDSS-2 subitem 7 (distressing hallucinations) and SCOPA-AUT subitem 11 (weak stream of urine) were significant determinants for pRBD. Our study showed that PD patients with pRBD had characteristic sleep and autonomic symptoms.